Pengaruh Pupuk ‘Mutiara’ dan Giberelin Terhadap Pertumbuhan dan Produksi Tanaman Semangka Partenocarpi - Arifin, Yuyun; Riry, John; Lawalata, Imelda J (Universitas Pattimura, 2024)
Watermelon production is influential in supporting the increase of income of the farm. Watermelon production tends to decline at present, so that efforts need to be carried out to optimize the growth and yield of watermelon plants. One of the important nutrients source for watermelon plants is ‘Mutiara’ fertilizer and the plant growth regulator (PGR) gibberellin. This study aimed to determine the right combination of ‘Mutiara’ fertilizer dosage and gibberellin concentration on the growth and yield of parthenocarpic watermelon plants. This research was conducted from September to December 2023 at Pattimura Mutiara Farm of Pattimura University, in Rumahtiga Village, Teluk Ambon Subdistrict, Ambon City. This research was an experimental study that used a Factorial Randomized Group Design (RAK) consisting of two treatment factors, i.e.: ‘Mutiara’ fertilizer with 4 levels and the dose of gibberellin with 4 levels, with replications, so that there was a total of 48 treatment combinations. The observed variables included plant height, number of leaves, number of female flowers formed, fresh fruit weight, fruit diameter, and number of seeds. The results showed that the interaction between the dose of ‘Mutiara’ fertilizer 6 g/plant and the concentration of gibberellin 6 mL/L was the best treatment combination and could increase plant length and number of leaves. The combination of 2 g of ‘Mutiara’ fertilizer and 2 mL/L gibberellin concentration was the best combination for fresh fruit weight